(untitled) (Journal of Information Technologies in Education (ITE), 2011)
One of directions of informatization of education is development and introduction of electronic textbooks for providing of independent work of students. The article is devoted to the report about creation of electronic textbook from the school course of ukrainian literature with the method of its teaching. General description of his component parts is given.